Preparation method and application of (111) interplanar spacing compressed platinum-based metal catalyst
By doping the modified carbon nanotube carrier with nitrogen atoms, the crystal surface compression of Pt(111) is achieved, which solves the problem of slow cathodic oxygen reduction reaction speed in hydrogen fuel cells, improves the electrocatalytic activity of the catalyst and the load of Pt, and reduces the The energy barrier is improved and the overall efficiency of hydrogen fuel cells is improved.
Patent Information
- Application Number
- CN202411377200.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The kinetic speed of cathode oxygen reduction reaction in existing hydrogen fuel cells is slow, resulting in the high cost and scarcity of the precious metal catalyst platinum, and the Pt(111) crystal surface structure is easily affected, affecting the performance of the catalyst.
Modified carbon nanotubes by doping nitrogen atoms to form Pt-N bonds, achieving Pt(111) crystal surface compression, improving the electrocatalytic performance of the catalyst, and replacing the metal oxide support with carbon nanotube support, enhancing Pt nanoparticles uniform dispersion and stability.
The electrocatalytic activity and oxygen reduction activity of the catalyst are improved, the energy barrier of the oxygen reduction reaction is reduced, the load and stability of Pt are enhanced, and the overall efficiency of the hydrogen fuel cell is improved.
Smart Images

Figure CN119252941A_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of hydrogen energy materials, and in particular to a preparation method and application of a (111) crystal plane spacing compressed platinum-based metal catalyst. Background technology:
[0002] Hydrogen fuel cells have been considered as the next generation engine for automobiles, stationary power, portable power and other power sources. However, due to the multi-step electron transfer and low mass transfer efficiency involved in the cathode oxygen reduction reaction (ORR), its kinetics are slow and requires the use of a large amount of precious metal catalysts, mainly platinum (Pt). For decades, Pt-based materials have been considered the most effective catalysts on the cathode of fuel cells, especially in proton exchange membrane fuel cells (PEMFC) in acidic media. So far, the widespread application of PEMFC is still hindered by the high cost and scarcity of Pt metal, prompting people to find innovative ways to improve Pt catalytic efficiency and reduce Pt utilization.
[0003] The Pt(111) crystal plane is the most effective lattice for adsorbing oxygen and oxygen reduction intermediates due to its tightly packed atomic structure, thus promoting the intrinsic oxygen reduction activity of the catalyst. However, the Pt(111) surface interface can be significantly affected by structural modifications, changing the electronic and geometric properties of the catalyst, which in turn affects the adsorption / desorption and reaction rate of oxygen reduction intermediates on the catalyst surface interface. Strain engineering is a technique that introduces lattice distortion or deformation into catalyst materials and has become a powerful tool for adjusting the catalytic performance of Pt-based electrodes. The strain effect can be induced by a variety of means, such as synthesis methods or the introduction of support materials. Among them, the research on the introduction of support materials is of great significance because battery electrode catalysts often use various supports to better disperse active sites and minimize the use of precious metal Pt. Summary of the invention:
[0004] The purpose of the present invention is to provide a preparation method and application of a (111) crystal plane spacing compressed platinum-based metal catalyst.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a (111) interplanar spacing compressed platinum-based metal catalyst, the method comprising the following steps:
[0007] (1) mixing carbon nanotubes and nitrogen-based materials in an aqueous solution at a mass ratio of 1:6 to 1:12, preferably 1:10, heating and refluxing at 60-65° C. for 6-8 h, cooling to room temperature and filtering;
[0008] (2) calcining the filtered solid obtained in step (1) at 500-700° C. in a nitrogen atmosphere, and cooling to room temperature to obtain nitrogen-doped carbon nanotubes;
[0009] (3) forming a mixed solution of the nitrogen-doped carbon nanotubes obtained in step (2) and a platinum metal precursor, and drying the mixed solution in a vacuum at 50-70° C.;
[0010] (4) grinding the mixture obtained in step (3) with a ball mill, washing it and drying it in a vacuum oven at 50-70° C.;
[0011] (5) reducing the powder obtained in step (4) at a high temperature of 500-700° C. in a reducing atmosphere to obtain the surface-compressed Pt-based metal electrocatalyst.
[0012] Preferably, the nitrogen-based material in step (1) is one or more of hydrazine hydrate, urea, and melamine, the heating reflux temperature is 60° C., and the reflux time is 8 hours.
[0013] Preferably, the calcination temperature in step (2) is 700° C. and the calcination time is 2 h.
[0014] Preferably, the platinum metal precursor in step (3) is an alcohol-soluble platinum group metal precursor, including one or more of chloroplatinic acid hydrate, chloroplatinate, and platinum acetylacetonate.
[0015] Preferably, the vacuum drying temperature in step (4) is 60° C. and the drying time is 24 h.
[0016] Preferably, the reducing atmosphere in step (5) is a hydrogen / argon mixed gas at a temperature of 700°C.
[0017] The preparation method above improves the dispersion effect of carbon nanotubes by doping nitrogen atoms in nitrogen-based materials, and uniformly loads Pt-based metal nanoparticles onto the surface of modified carbon nanotubes. Chemical bonds are formed between nitrogen atoms and Pt components, so that the Pt (111) crystal plane of Pt nanoparticles with a particle diameter between 2 and 8 nm is compressed, and the compression is a planar (2D) compression, thereby improving the electrocatalytic performance of platinum-based metals.
[0018] Therefore, the present invention also protects the use of the (111) crystal plane spacing compressed platinum-based metal catalyst obtained by the above preparation method in hydrogen fuel cells (PEMFC), which is used as a cathode oxygen reduction catalyst of PEMFC.
[0019] The beneficial effects of the present invention are as follows:
[0020] (1) The present invention realizes the (111) crystal plane compression effect of the Pt-based electrocatalyst through nitrogen atom doping modification, and expands the crystal plane spacing compression of the Pt-based metal catalyst carrier from metal oxide to carbon nanotube carrier.
[0021] (2) The present invention applies compressive strain to the Pt(111) surface through nitrogen atom doping modification, weakens the binding energy of oxygen reduction intermediates, makes H2O more easily desorbed on the catalyst surface, and thus improves the electrocatalytic activity of the catalyst.
[0022] (3) The present invention reduces the loss of Pt components and increases the Pt component loading in the catalyst through low-temperature heating reflux, high-temperature calcination and grinding treatment.
[0023] (4) Doping carbon nanotubes with N atoms can increase the defect sites of carbon nanotubes and thus improve the uniform dispersion of Pt active components on the surface of carbon nanotube carriers.
[0024] (5) The formation of Pt-N bonds between N atoms and Pt components not only helps to increase the Pt loading, but also effectively improves the stability of the Pt active component; it can also serve as an active site to improve the oxygen reduction activity of the catalyst.
[0025] In summary, the present invention improves the defect sites of carbon nanotubes through nitrogen atom doping modification, thereby improving the uniform dispersion of Pt active components on the surface of carbon nanotube carriers, and forming Pt-N bonds between N atoms and Pt components, which is not only beneficial to increasing the Pt loading, but also effectively improving the stability of Pt active components; it can also serve as an active site, realizing the (111) crystal plane compression effect of Pt-based electrocatalysts, weakening the binding energy of oxygen reduction intermediates, making H2O more easily desorbed on the catalyst surface, thereby improving the electrocatalytic activity of the catalyst, and the prepared (111) crystal plane spacing compressed Pt-based metal catalyst is used as a PEMFC cathode catalyst, which can reduce the energy barrier in the oxygen reduction reaction, weaken the binding energy of oxygen reduction intermediates, and accelerate the desorption rate of H2O on the catalyst surface, thereby improving the overall efficiency of PEMFC. Description of the drawings:
[0026] Figure 1 Characterization diagram of the crystal plane compressed Pt-based metal electrocatalyst (labeled as Pt / N-CNT) prepared in Example 1, where ac is a transmission electron microscope (TEM) photograph, and df is the C, Pt, and N element distribution diagrams (EDS), respectively. It can be seen that the N element is uniformly doped into the CNT, and the Pt element is uniformly distributed on the surface of the N-CNT carrier.
[0027] Figure 2 This is a TEM image of the undoped carbon nanotube-supported Pt-based catalyst (labeled as Pt / CNT) prepared in Comparative Example 1. It can be seen that compared with the catalyst Pt / N-CNT in Example 1, the Pt particles in the Pt / CNT catalyst in Comparative Example 1 are unevenly dispersed and agglomerated.
[0028] Figure 3Spectra of the catalysts of Example 1 and Comparative Example 1. Wherein, a is the N1S spectrum of the catalyst Pt / N-CNT in Example 1, and there is a Pt-N chemical bond at 399.4 eV, indicating that there is a strong metal-carrier interaction between Pt / N-CNT; b is the Pt 4f spectrum of the catalysts of Example 1 and Comparative Example 1. Compared with the Pt / CNT catalyst in Comparative Example 1, the Pt 4f spectrum of the Pt / N-CNT catalyst in Example 1 shifts to a low binding energy, indicating that the N doped in the N-CNT carrier provides more electrons for the Pt active component, and the result is consistent with the presence of oxidized N in the N1s spectrum.
[0029] Figure 4 The high-resolution transmission electron microscopy (HR-TEM) images of the catalysts of Example 1 and Comparative Example 1. Among them, a is a local high-resolution TEM image of the Pt / N-CNT catalyst, b is a fine image of the box in Figure a, and c is a schematic diagram of the compression of the (111) crystal surface of the Pt / N-CNT catalyst; correspondingly, d is a local high-resolution TEM image of the Pt / CNT catalyst, e is a fine image of the box in d, and c is a schematic diagram of the compression of the (111) crystal surface of the Pt / CNT catalyst; through the fine structure analysis of the HR-TEM image, the U axis and V axis of the (111) surface of the Pt / N-CNT catalyst particles in Example 1 are respectively and The lattice spacing is The angle is 126°; while in Comparative Example 1, the U axis and V axis of the (111) plane of the Pt / CNT catalyst particle are and The lattice spacing is The angle is 122.5°. Therefore, compared with the Pt / CNT catalyst of Comparative Example 1, the compressive strain of the Pt / N-CNT catalyst in Example 1 in the two-dimensional plane is 6.3% (2D plane compression), proving that N atom doping can produce Pt (111) crystal plane compressive strain.
[0030] Figure 5 The electrochemical performance test of the catalysts of Example 1 and Comparative Example 1 was performed by linear sweep voltammetry (LSV). Compared with the catalyst Pt / CNT of Comparative Example 1, the polarization curve of the catalyst Pt / N-CNT in Example 1 was positively shifted, and the half-wave potential was 21 mV, as shown in FIG. Figure 4 As shown in a; Tafel curve is as follows Figure 3 As shown in b, the Tafel slope of the catalyst Pt / N-CNT in Example 1 is 47.8 mV / dec, which is less than 65.4 mV / dec of the catalyst Pt / CNT in Comparative Example 1, indicating that the Pt / N-CNT catalyst with crystal plane compression has better oxygen reduction activity.
[0031] Figure 6The XRD spectra and parameters of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2, wherein a is the XRD spectra of the catalysts of Example 1 and Comparative Example 1 and the standard Pt(111) spectrum (PDF#70-2431) of Comparative Example 2, and b is the Pt(111) crystal plane parameter of Comparative Example 2.
[0032] Figure 7 TEM images and structural analysis of Comparative Example 3. Among them, a is a photo of the catalyst of Comparative Example 3, b is a HR-TME image, and c is a local fine structure analysis of b. From c, it can be seen that the interplanar spacing of Comparative Example 3 is It is basically consistent with the uncompressed crystal plane spacing and the catalyst crystal plane spacing parameters in the reference patent CN 114068967A. Specific implementation method:
[0033] The following is a further description of the present invention, rather than a limitation of the present invention.
[0034] Embodiment 1:
[0035] This embodiment prepares a crystal plane compressed Pt-based metal catalyst under optimal conditions.
[0036] First, 100 mL of 30% hydrazine hydrate was mixed with 100 mL of deionized water, and 500 mg of carbon nanotubes (CNT, mass ratio of carbon nanotubes to hydrazine hydrate was 1:10) was added under stirring; the mixed solution was heated to reflux at 60°C for 8 h, cooled to room temperature and then filtered; the filtered solid was heated and calcined at 700°C in a N2 atmosphere for 2 h, and cooled to room temperature to obtain nitrogen-doped carbon nanotubes (N-CNT).
[0037] The Pt / N-CNT catalyst was synthesized by a method combining grinding and calcination. Chloroplatinic acid hydrate (H2PtCl6·6H2O, Pt≥37.5%) was dissolved in ethanol, and the above-mentioned N-CNT was added to the Pt precursor solution under stirring conditions; the mixture was vacuum dried at 60°C for 24 hours, and then the solid mixture was ground into powder using a ball mill; the powder was rinsed with deionized water several times and dried at 60°C under vacuum conditions for 24 hours; finally, the powder was calcined at 700°C for 5 hours in a H2 reducing atmosphere to obtain a Pt / N-CNT catalyst.
[0038] Secondly, the crystal surface compressed Pt-based metal electrocatalyst in this embodiment is equipped with catalyst ink and tested with a three-electrode system for linear sweep voltammetry (LSV). The test conditions are: O2-saturated H2SO4 solution, concentration is 0.5M; rotating disk electrode diameter is 5 mm, rotation speed is 1600rpm; scanning voltage range is 0-1.2V (vs.RHE), scanning rate is 10mV s-1. The results are shown in Figure 2. Figure 5 shown.
[0039] Comparative Example 1:
[0040] The Pt / CNT catalyst was synthesized by the same method and conditions as in Example 1, except that the nitrogen-doped carbon nanotube N-CNT carrier was replaced with carbon nanotube CNT, and the other conditions were the same. Figure 2 , Figure 3 and Figure 4 The electrochemical performance curve is shown in Figure 5 shown.
[0041] Comparative Example 2:
[0042] In order to better understand the compression effect of carbon nanotubes and heteroatom-doped carbon nanotubes on the Pt(111) crystal plane, according to the XRD characterization results of Example 1 and Comparative Example 1, the Pt(111) crystal plane of the XRD standard card is used as Comparative Example 2. The Bragg X-ray diffraction equation can be used to calculate that the lengths of the U axis and V axis of the standard Pt(111) crystal plane are both The interplanar spacing is The angle is 120°, and the result is Figure 6 shown.
[0043] Comparative Example 3:
[0044] Refer to Example 1, except that the nitrogen-doped carbon nanotubes are replaced by N-doped porous carbon. The preparation method of the N-doped porous carbon is referred to Example 1 in CN 114068967 A. The obtained catalyst is recorded as Pt / NC. Its TEM image and structural analysis are shown in Figure 7 .from Figure 7 It can be seen from c that the interplanar spacing of Comparative Example 3 is The uncompressed crystal plane spacing is basically consistent with the crystal plane spacing parameters of the catalyst in the reference patent CN 114068967A. By comparing Example 1 with Comparative Example 3, it can be seen that nitrogen-doped carbon nanotubes can improve the crystal plane compression effect compared with N-doped porous carbon.
[0045] Compared with Comparative Example 2, the Pt(111) crystal plane compression effect of the Pt / CNT catalyst in Comparative Example 1 is 8.8%, and the Pt(111) crystal plane compression effect of the Pt / N-CNT catalyst in Example 1 is 14.6%. This further illustrates that the carbon nanotube-supported Pt-based catalyst prepared by the method is conducive to crystal plane compression, and heteroatom-doped carbon nanotubes can further improve the crystal plane compression effect.
[0046] Finally, it should be noted that the above are only preferred embodiments of the present invention. For those skilled in the art, the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents, or some of the operating steps can be improved. Any modification, replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a (111) interplanar spacing compressed platinum-based metal catalyst, characterized in that: The method comprises the following steps: (1) mixing carbon nanotubes and nitrogen-based materials in an aqueous solution at a mass ratio of 1:6 to 1:12, heating under reflux at 60-65° C. for 6-8 h, cooling to room temperature and filtering; (2) calcining the filtered solid obtained in step (1) at 500-700° C. in a nitrogen atmosphere, and cooling to room temperature to obtain nitrogen-doped carbon nanotubes; (3) forming a mixed solution of the nitrogen-doped carbon nanotubes obtained in step (2) and a platinum metal precursor, and drying the mixed solution in a vacuum at 50-70° C.; (4) grinding the mixture obtained in step (3) with a ball mill, washing it and drying it in a vacuum oven at 50-70° C.; (5) reducing the powder obtained in step (4) at a high temperature of 500-700° C. in a reducing atmosphere to obtain the surface-compressed Pt-based metal electrocatalyst.
2. The preparation method according to claim 1, characterized in that: The nitrogen-based material in step (1) is one or more of hydrazine hydrate, urea, and melamine, and the heating reflux temperature is 60° C. and the reflux time is 8 hours.
3. The preparation method according to claim 1, characterized in that: The carbon nanotubes and the nitrogen-based material are mixed in an aqueous solution at a mass ratio of 1:
10.
4. The preparation method according to claim 1, characterized in that: The calcination temperature in step (2) is 700° C. and the calcination time is 2 h.
5. The preparation method according to claim 1, characterized in that: The platinum metal precursor in step (3) is an alcohol-soluble platinum group metal precursor, including one or more of chloroplatinic acid hydrate, chloroplatinate, and platinum acetylacetonate.
6. The preparation method according to claim 1, characterized in that: The vacuum drying temperature in step (4) is 60° C. and the drying time is 24 h.
7. The preparation method according to claim 1, characterized in that: In step (5), the reducing atmosphere is a hydrogen / argon mixed gas at a temperature of 700°C.
8. Use of the (111) crystal plane spacing compressed platinum-based metal catalyst obtained by the preparation method of claim 1 in a hydrogen fuel cell as a cathode oxygen reduction catalyst.
Citation Information
Patent Citations
Platinum-containing bimetallic electrode catalyst using carbon-nitrogen nano tube as carrier and preparation method
CN101480612A
Nitrogen-doped carbon nanotube-nickel-doped molybdenum nitride composite material and preparation method and application thereof
CN117966202A
Porous carbon materials, nanoparticles, methods of making same, and uses thereof
US20230271840A1
